2013
DOI: 10.1111/epi.12310
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of epileptic syndromes with fixation off sensitivity persisting in adult life

Abstract: PurposeThe term fixation off sensitivity (FOS) was proposed by Panayiotopoulos to describe epilepsy/electroencephalography (EEG) changes evoked by the suppression of central vision and fixation. The EEG pattern usually consists of spike/polyspike and waves localized in occipital regions. FOS occurs mainly in children with idiopathic occipital partial epilepsies and rarely in adults. In this retrospective study we evaluated the clinical data, EEG, and magnetic resonance imaging (MRI) findings of patients with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 15 publications
(21 reference statements)
2
16
0
Order By: Relevance
“…However we could not completely rule out the possibility of combined scotosensitivity, we used the term "FOS with or without scotosensivity" here. Although the underlying mechanisms remain still uncertain due to its rarity, FOS is thought to be modulated by α-rhythm generators and influenced by cortical hyperexcitability [4]. In MELAS syndrome, epileptic seizures occur primarily in association with stroke-like episodes, however, they can happen in patient with normal brain MRI like our patient.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However we could not completely rule out the possibility of combined scotosensitivity, we used the term "FOS with or without scotosensivity" here. Although the underlying mechanisms remain still uncertain due to its rarity, FOS is thought to be modulated by α-rhythm generators and influenced by cortical hyperexcitability [4]. In MELAS syndrome, epileptic seizures occur primarily in association with stroke-like episodes, however, they can happen in patient with normal brain MRI like our patient.…”
Section: Discussionmentioning
confidence: 69%
“…Although FOS is rarely seen in the adult population, it often represents the EEG expression of symptomatic epilepsies (cortical malformations, celiac disease, calcified vascular malformation, and stroke, etc.) [4]. Strictly speaking, we should have differentiated FOS with scotosensitivity by the elimination of central vision/fixation in the presence of light with the use of modified Ganzfeld stimulation or Frenzel lenses.…”
Section: Discussionmentioning
confidence: 99%
“…The classification of the epilepsy presentations was reported in 45 of the articles [8, 10, 11, 13, 15, 16, 1922, 2530, 32, 33, 36, 38, 41–44, 48, 49, 51, 54, 56, 57, 6069, 74, 75, 77, 81, 8688,, 6069, 74, 75, 77, 81, 8688]. Of these, 25 could be used to calculate the prevalence of focal epilepsy amongst patients with epilepsy [8, 13, 15, 16, 18–21, 28, 33, 36, 41, 43, 45, 48, 51, 54, 56, 57, 61, 63, 65, 74, 87, 88].…”
Section: Resultsmentioning
confidence: 99%
“…Koutromanidis, et al in the analysis of their videotelemetric data found both generalized and focal epilepsies contribute to the expanding repertoire of this evolving electroclinical syndrome [4]. The overwhelming contribution of the occipital lobe even in patients not fitting into the syndromic description of occipital lobe epilepsies of childhood was substantiated through the appraisal of electrical and functional imaging data by them and other investigators [4,6,7]. Secondary causes were excluded by imaging and celiac work up.…”
Section: Discussionmentioning
confidence: 99%
“…However, this electrographic finding is not specific for any of the entities within this broad and versatile category of epilepsies. There is a predilection for the younger age group [2][3][4][5][6]. This case report and ensuing discussion focuses on the clinical diagnosis, pathophysiology and differentials of this electro clinical syndrome.…”
Section: Introductionmentioning
confidence: 99%